(untitled) (Experimental biology, 2021)
Over the past decade, consumers’ approach to healthy nutrition has changed dramatically, and today, particular importance is attached to increasing the life expectancy of the population through the consumption of healthy foods. The general deterioration in population health, a decrease in resistance to infections, and the widespread spread drug resistance of pathogens require the development of healthy products preventing pathogenic microorganisms’ growth and increasing the body’s defense. Dairy products have a significant place in the functional food market, and functional milk-based drinks are a growing segment of this sector. An association of lactic acid bacteria Lactobacillus paracasei 4m-2b, Lactobacillus fermentum A15, acetic acid bacteria Acetobacter fabarium 4-4M, and lactose-fermenting yeast Kluyveromyces marxianus 4МА, which has antagonistic activity against fungal and bacterial cultures from the genera Escherichia, Salmonella, Sarcina, Mycobacterium, Candida, Fusarium, Penicillium was used as a starter for the beverage. Wheat bran containing significant amounts of insoluble dietary fiber was used as a prebiotic additive. To improve the sensory properties, biological and nutritional values, ​​and to expand the spectrum of antagonistic activity of the starter microorganisms, various plant supplements were used. Variants of fermented milk drinks with the addition of yeast and without yeast were obtained. A higher antagonistic activity of beverage variants not including Kluyveromyces marxianus 4MA in the starter culture was shown against Salmonella enterica Serotype Dublin. However, suppression of Candida albicans B514 was most effective in the absence of yeast in the starter culture. The best variant of a whey-based synbiotic beverage with wheat bran and addition of raspberries, millet and mare’s milk has been selected. The resulting fermented beverage was characterized by high sensory characteristics and a wide spectrum of bacterial and fungal test cultures inhibition. Key words: whey, functional symbiotic beverage, antibacterial activity, antifungal activity, plant supplements, mare’s milk, probiotic, prebiotic.